Infection control measures to reduce hospital infection rates in the medical city burn center - albermani, mohannad; Salman, Waleed A.; Hamad, Gulala K.; Hadi, Eman A. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: The most serious problem in burn units is nosocomial infection (NI). In extensive burn patients, sepsis is considered the main cause of death; infection control program will help to lower NI and its subsequent high mortality rate. Objective: To achieve the lowering of NI in burn units, by effect of infection control measures (ICMs). Patients and methods: This is a prospective study conducted on patients admitted in Burn Center/Medical City in Baghdad from May 2012 to April 2015. A total of 1977 hospitalized patients were included in this study. This center receives burn patients with different severity. In around April 2012 an infection control program was started in the center by the infection control team ICT. Results: The rate of NI was reduced; the mortality rates declined, and mean hospital stay of NI patients decreased. The number of cases with burn wound infection (BWI), bacteremia sepsis and subsequent mortality were decreased. Conclusion: ICMs helped to reduce NIs in the burn center .Rational usage of antibiotic and baths, new dressing, early excision and grafting are vital and recommended.